RAW MATERIALS IN INDUSTRY AND ITS PROPERTIES - Olchinboyev Otabek; Egamberdiyev Shavkatbek (Journal of Artificial Intelligence and Digital Economy, 2024)
This article provides detailed information about raw materials used in industry. In addition, the types, characteristics and classifications of industrial raw materials are presented. Feedback on improving and updating the properties of raw materials used in industry has been given.